2002
DOI: 10.1128/iai.70.12.6606-6613.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with a Combination of Merozoite Surface Proteins 4/5 and 1 Enhances Protection against Lethal Challenge withPlasmodium yoelii

Abstract: It is widely believed that subunit vaccines composed of multiple components will offer greater protection against challenge by malaria, and yet there is little experimental evidence to support this view. We set out to test this proposition in the Plasmodium yoelii challenge system in rodents by comparing the degree of protection conferred by immunization with a mixture of merozoite surface proteins to that conferred by single proteins. We therefore examined a defined protein mixture made of the epidermal growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…Importantly, we have demonstrated that oral immunization with recombinant PyMSP4/5 plus PyMSP1 19 induces antibodies to both antigens and also provides enhanced protection against parasite infection. These data are consistent with those achieved by parenteral immunization (8) and provide a rationale for developing multicomponent oral vaccines.…”
supporting
confidence: 68%
“…Importantly, we have demonstrated that oral immunization with recombinant PyMSP4/5 plus PyMSP1 19 induces antibodies to both antigens and also provides enhanced protection against parasite infection. These data are consistent with those achieved by parenteral immunization (8) and provide a rationale for developing multicomponent oral vaccines.…”
supporting
confidence: 68%
“…When SGV-H2 was evaluated in an infectious challenge model it was much more effective than the single-gene plasmids confirming the previously demonstrated advantage of multi-antigenic vaccines. 4,5 The SGV-H2 in this experiment also produced better protection than the plasmid mixture although the reason is unclear and may require further experimentation to determine if the difference is significant. Nevertheless, from the infectious challenge studies, the SGV-H2 shows good potency based on its multi-antigenic nature.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 98%
“…3 Evidence suggests that a broad immune response composed of multiple antigens is more protective than a narrow focused response. 4,5 Since a single protective antigen has not been identified for many diseases, a strategy of delivering multiple antigens would, therefore, have an enhanced likelihood of success by increasing the number of potential antigens. For commercial purposes, the cost, formulation and manufacturing issues could limit the feasibility of delivering a mixture of single-gene DNA vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…(GST-PyMSP1 19 ) or as a hexahistidine-tagged fusion in Saccharomyces cerevisiae (yPyMSP1 19 ) (20,38). To generate PyMSP1 19 -specific antibodies, two female New Zealand White rabbits were injected subcutaneously with 100 g of GSTPyMSP1 19 or 50 g of yPyMSP1 19 , emulsified in complete Freund's adjuvant.…”
Section: Generation Of Rabbit Anti-pymsp1 19 Antibodies Pymsp1 19 Wamentioning
confidence: 99%
“…Immunization of mice with recombinant PyMSP1 19 and the subsequent challenge infection were performed as previously described (20,39). Briefly, BALB/c mice (females, 6 to 8 weeks old) were immunized intraperitoneally with 25 g or 10 g of purified recombinant PyMSP1 19 emulsified in complete Freund's adjuvant.…”
Section: Generation Of Rabbit Anti-pymsp1 19 Antibodies Pymsp1 19 Wamentioning
confidence: 99%